New efficient FFT algorithm and pipeline implementation results for OFDM/DMT applications - Jung, Yunho; Yoon, Hongil; Kim, Jaeseok (IEEE transactions on consumer electronics, 2003)
In this paper, we propose a new efficient FFT algorithm for OFDM/DMT applications and present its pipeline implementation results. Since the proposed algorithm is based on the radix-4 butterfly unit, the processing rate can be twice as fast as that based on the radix-23 algorithm. Also, its implementation is more area-efficient than the implementation from conventional radix-4 algorithm due to reduced number of nontrivial multipliers like using the radix-2/sup 3/ algorithm. In order to compare the proposed algorithm with the conventional radix-4 algorithm, the 64-point MDC pipelined FFT processor based on the proposed algorithm was implemented. After the logic synthesis using 0.35 /spl mu/m CMOS technology, the logic gate count for the processor with the proposed algorithm is only about 70% of that for the processor with the conventional radix-4 algorithm. Since the proposed algorithm can achieve higher processing rate and better efficiency than the conventional algorithm, it is very suitable for the OFDM/DMT applications such as the WLAN, DAB/DVB, and ADSL/VDSL systems.